IDENTIFICATION OF TORCH PATHOGENS IN CONGENITAL CATARACT PATIENTS VISITING ARMED FORCES INSTITUTE OF OPHTHALMOLOGY: Torch Pathogens in Congenital Cataract - Javaid, Mamoona; Masud, Hannan; Sajjad Rathore, Hassan; Ali, Dilshad; Javaid, Haroon (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the rate of positivity of Toxoplasma gondii, Rubella, Cytomegalovirus, Herpes simplex (TORCH) pathogens in patients suffering from congenital cataract in Pakistan.Study Design: Cross sectional comparative study.Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi, from Jun 2017 to Mar 2018.Methodology: Cataract group included sixty children already diagnosed with congenital cataract and control group included 60 children not suffering from congenital cataract. Serum samples of all children were collected to test against IgG and IgM antibodies of Toxoplasma gondii, Rubella, Cytomegalo, Herpes simplex pathogens using enzyme linked immune essay (ELISA) technique. Data were analyzed observe in difference between unilateral and bilateral cataract and between cataract and control group.Results: Out of 60 children in cataract group, 29 were tested positive for Toxoplasma gondii, Rubella, Cytomegalo (CMV), Herpes simplex infections. CMV IgG antibodies were identified in 21 (35%) children followed by Rubella IgG 13 (21.7%), Toxoplasmosis IgG 8 (13.3%), CMV IgM 7 (11.7%), HSV I IgG 5 (8.3%), HSV II IgG 2 (3.3%) and HSV I IgM 1 (1.7%) antibodies. None of the children was positive for Toxoplasmosis, Rubella and HSV II IgM antibodies. There was no statistical difference in rate of positivity of Toxoplasma gondii, Rubella, Cytomegalovirus, Herpes simplex pathogens between unilateral and bilateral cataract and between cataract and control group.Conclusion: Toxoplasma gondii, Rubella, Cytomegalovirus, Herpes simplex pathogens are an important cause of congenital cataract with Cytomegalovirus and Rubella virus being most common respectively. In order to prevent paediatric complications, we need........